Bullous Fixed Drug Eruption Probably Induced by Paracetamol - Agarwala, Manoj Kumar (Indian J Dermatol, 2016)
We report a case of a 42-year-old male who presented with second episode of bullous eruptions after ingestion of paracetamol. There were no systemic complaints. The temporal correlation with the drug, history of a similar episode and the quick improvement led us to a diagnosis of bullous fixed drug due to paracetamol. Applying Naranjo's algorithm, a causality score of 8 was obtained and was categorized as probable reaction to paracetamol. Clinicians should be vigilant of the possible adverse reactions to drugs with robust safety profiles. Drug alert cards could play an important role in preventing recurrences.